Celiacomesenteric trunk - (:unkn) unknown (My University, 1997)
The celiac trunk is the widest ventral branch of the abdominal aorta. The unusual embryological development of the ventral splanchnic arteries can lead to considerable variations. During the dissection of a 54-year-old male cadaver as a rare variation, a celiacomesenteric trunk was observed. The rare occurrence of this variation is staled to be 1%-27%. As in the other case, the celiac trunk and the superior mesenteric arteries arose from a common trunk at the level of L1. This case of celiacomesenteric trunk is described in detail, which can be of value in the operative procedures of the upper abdomen.
Keywords: Celiacomesenteric trunk; Variations